Optimization of Strategy Implementation of Financial Governance in an Effort To Improve The Quality of Financial Reporting in The People's Consultative Assembly (MPR - RI) - Rina Anugrahaeni; Azhar Affandi; Ellen Rusliati (LP2M IAIN Palopo, 2025)
The People's Consultative Assembly (MPR) is a strategic high-state institution with constitutional functions that support accountable financial governance (Law of the Republic of Indonesia, 2003). Good financial governance in government institutions has become increasingly crucial, and the quality of financial reporting in the MPR-RI is often linked to the enhancement of public trust in the management of government finances. This research aims to evaluate the presentation of financial statements at the People's Consultative Assembly by analyzing financial governance, evaluating the presentation of financial statements, identifying what obstacles are faced in financial governance, and formulating optimal strategies that need to be implemented in good financial governance. The data in the present research was processed and scrutinized employing qualitative methods and strategy formulation with SWOT analysis. There are some conclusions obtained that the financial report of MPR-RI is currently in a good position, with a WTP status obtained from BPK. The results of the SWOT analysis in the context of MPR RI's financial governance are located in Quadrant 2, with a SW value of 0.03 and an OT value of -0.04. This result leads to a recommended strategy of diversification or defensive strength, which means that the MPR RI has good internal strength in financial management, but faces external threats (such as public pressure, changes in regulations, budget constraints, or national political dynamics). Some of the resulting recommendations are strengthen the security of data and financial application systems (SAKTI) using encryption and role-based authorization to prevent access breaches, utilize the advantages of internal oversight (Inspectorate and SPIP) to ensure consistent implementation of regulations across units, leverage external audits by the BPK to anticipate reporting discrepancies and encourage compliance with timelines, develop SOPs and cross-unit coordination protocols based on the successful experiences of existing reporting and oversight systems, and be responsive to technological changes by forming a special digital adaptation team in the financial sector.